Cyber-physical systems and industry 4.0 : practical applications and security management - Goyal, Dinesh, 1976-; Balamurugan, S. (Shanmugam), 1985-; Senthilnathan, Karthikrajan, 1991-; Annapoorani, Iyswarya, 1976-; Israr, Mohammad (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2022)
"Cyber-Physical Systems and Industry 4.0: Practical Applications and Security Management explores the growth of information and communication technologies (ICT) with an emphasis on cyber-physical systems (CPS) and security management of these systems. This volume discusses and analyzes the various effective practical applications of cyber-physical systems, which involves the integration of the physical process with embedded computation, controller, and network monitoring along with the feedback loop from physical systems. The authors identify the best set of applications and discuss the drawbacks of existing systems. The book provides a broad outlook on the applications of cyber-physical systems along with case studies and examples in healthcare, automotive electronics, industrial automation, environment monitoring, agriculture, and applications in civil and mechanical sectors. Topics include using an energy management system in smart grids, implementing an intelligent traffic management system, warehouse tracking and monitoring, medical cyber-physical systems security, remote healthcare monitoring, and more. With the the field of CPS advancing so rapidly, this volume will be valuable for researchers, system designers, and practitioners to keep abreast of new developments in the field along with the important security management implications."--
Energy Management System in Smart Grids: A Cyber-Physical System Approach / J. Arun Venkatesh, K. Iyswarya Annapoorani, and Ravi Samikannu -- An Intelligent Traffic Management System / M. Gowtham, M. K. Banga, Mallanagouda Patil, and Natarajan Meghanathan -- Real-Time Monitoring and Tracking of Intrusions in Warehouses Using Video Analytics Techniques / Jeeva S., Sivabalakrishnan M., Sarangam Kodati, and Hong-Seng Gan -- Internet of Things: Applications, Vulnerabilities, and the Need for Cyber Resilience / V. Karpagam, A. Kayalvizhi, Naveen Bharathi, S. Balamurugan -- Medical Cyber-Physical Systems Security / R. Rekha -- Secure Data Aggregation Using Cyber-Physical Systems for Environment Monitoring / M. K. Sandhya, K. Murugan, and S. Prasidh -- RTLS: An Introduction / M. Senthamil Selvi, K. Deepa, S. Balamurugan, S. Jansi Rani, and A. Mohamed Uvaze Ahamed -- Data Analytics and Its Applications in Cyber-Physical Systems / A. Sheik Abdullah, R. Parkavi, T. Saranya, P. Priyadharshini, and Arif Ansari -- Dual-Axis Solar Tracking and Monitoring of Solar Panel Using Internet of Things / Vijayan Sumathi, J. Kanagaraj, Siva Sarath Chandra Reddy, Sai Sujith Kankipati, Adarsh Vidavaluru, and Umashankar Subramaniam -- Demystifying Next-Generation Cyber-Physical Healthcare systems / Veeramuthu Venkatesh, Pethuru Raj, Sathish A. P. Kumar, Suriya Praba T, and R. Anushia Devi -- A Novel Cyber-Security Approach for Nodal Authentication in IoT Using Dual VPN Tunneling / N. M. Saravana Kumar, S. Balamurugan, K. Hari Prasath, and A. Kavinya -- Role of Detection Techniques in Mobile Communication for Enhancing the Performance of Remote Health Monitoring / Arun Kumar, Manoj Gupta, Mohit Kumar Sharma, Manisha Gupta, Laxmi Chand, and Kanchan Sengar -- Deep Learning in Agriculture as a Computer Vision System / M. Senthamil Selvi, K. Deepa, N. Saranya, and S. Jansi Rani -- Deep Learning: Healthcare / M. Senthamil Selvi, K. Deepa, S. Jansi Rani, and N. Saranya -- Infrastructure Health Monitoring Using Signal Processing Based on an Industry 4.0 System / Sameer Patel, Ajay Kumar Vyas, and Kamal Kant Hiran.
OCLC-licensed vendor bibliographic record.
Keywords: Cooperating objects (Computer systems); Cooperating objects (Computer systems) -- Industrial applications; Cooperating objects (Computer systems) -- Security measures; SCIENCE / Life Sciences / General